(untitled) (Informatica, 2022)
To enhance stream ciphers, numerous studies have concentrated on the randomness, unpredictable nature, and complexity of keystream. Numerous stream algorithms have been put forth. Most of them require a significant amount of computational power. Salsa20 is a high-performance stream encryption solution that works on computers with fewer resources and uses a secure method that is faster than AES. They suggest Salsa20 for encryption in common cryptographic applications. Users who value speed over certainty should utilize the Salsa20 family of reduced-round ciphers, such as the (8,12) round cipher. It uses a 256-bit key and a hash algorithm. A successful fusion makes use of both the Salsa20 algorithm’s and the random maps’ advantages to improve the Salsa20 algorithm’s shortcomings by increasing its unpredictability. Particularly now that Salsa20/7 has been hacked and Salsa20/12 is no longer as secure as it previously was. As a result, Salsa20 needs to achieve a high level of diffusion to withstand known attacks. Right now, salsa20 and its shortened versions rank among the fastest ciphers. This study presents a novel lightweight approach to construct a strong keystream that is sufficiently random to avoid being predicted by adversaries, achieve good diffusion, and withstand known assaults. A NIST test found that the performance of the (Salsa20-chaotic maps) approach in terms of data integrity and secrecy is nearly 0.3131 higher than that of the Salsa20.